Impact of interface recombination on direct-gap photoluminescence from Ge epitaxial layers on Si. (5th March 2019) - Yako, Motoki; Higashitarumizu, Naoki; Ishikawa, Yasuhiko
Abstract: Direct-gap photoluminescence (PL) at the wavelength around 1.55  μ m from Ge epitaxial layers on Si is studied toward Ge lasers in Si photonics. Comparing the PL intensities under two different wavelengths of excitation lasers, non-radiative interface recombination velocities are estimated to be as large as 10 5  cm s −1 at Ge/Si and Ge/air interfaces, whereas that at the Ge/GeO2 interface is estimated to be as small as 10 3 –10 4  cm s −1, which is required for the threshold current density in Ge lasers as low as 10 kA cm −2 . In order to remove the effect of defect-rich Ge/Si hetero-interfaces with a high recombination velocity, a wet chemical treatment in a CH3 COOH/HNO3 /HF/I2 solution is examined. A preferential etching of Ge at Ge/Si interfaces leads to an enhancement of the PL peak intensity by 83 times. A suppression of non-radiative recombination at the Ge/Si interface should contribute to this enhancement, and such a suppression plays a critical role for Ge lasers.